Observation of macro surface and gear mass of 3d printing machine using pla filament - Mochamad Edoward Ramadhan; Aris Zainul Muttaqin; M. Trifiananto (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2022)
3D Printing Machine is a machine that works with the basic principle of CNC, namely the movement of the machine in making the workpiece which is regulated by the G code in 3 coordinate axes x, y, and z. Based on how it works, 3d printing machines are classified into 7, namely, Vat photopolymerization, Material Extrusion, Powder-Bed Fusion, Sheet Lamination, Binder Jetting, Material Jetting, Directed Energy Deposition. The results of the research on 3d Printing Material extrusion this time using PLA material with a machining diameter of 1.75mm, nozzle distance with bed 0.1mm, nozzle diameter 0.4mm, layer height 0.12mm, nozzle temperature 2000C, bed temperature 600C, printing speed 80mm/s. The experimental results found problems such as clogging, the filament does not stick to the bed, the filament has a different freezing point, thus affecting the geometry of the workpiece to be printed. For the mass of all printed workpieces after measuring the mass with no significant changes, it is ensured that the problem originates from variables related to the printing of each layer in the form of printing speed, bed temperature, nozzle temperature, and system temperature.